Tolerance and mitigation strategies of proton exchange membrane fuel cells subject to acetylene contamination - Zhai, Yunfeng; St-Pierre, Jean (International journal of hydrogen energy, 2018)
Acetylene contamination in proton exchange membrane fuel cells (PEMFCs) significantly depends on cell operating conditions. In this work, acetylene contamination is studied by varying the acetylene concentration, cathode potential and temperature. Hysteresis in the cell performance response is observed during cycling tests with variations in acetylene concentration and cathode potential and is attributed to the potential dependency of acetylene redox reactions. The tolerance of PEMFCs to acetylene is established at approximately 23 ppm for a commercially available catalyst-coated membrane. For a cell poisoned by acetylene at a concentration above the tolerance value, performance losses are eliminated by bringing the ohmic compensated cell voltage into the acetylene oxidation (cell voltage increase) or hydrogenation (cell voltage decrease) regions. •Cycling C2H2 concentration or cathode potential causes voltage response hysteresis.•Hysteresis is attributed to the potential dependency of C2H2 redox reactions.•PEMFC tolerance to C2H2 is established at approximately 23 ppm.•Adjusting operation parameters mitigate C2H2 contamination effects.